Regional Economic Issues, April 2015, Europe : The Western Balkans: 15 Years of Economic Transition. (Regional Economic Outlook, 2015)
This report analyses the main economic developments and achievements in the Western Balkan countries, and lays out the key macroeconomic policy challenges for the future.